2022
DOI: 10.1057/s41599-022-01038-2
|View full text |Cite
|
Sign up to set email alerts
|

Topic modelling exposes disciplinary divergence in research on the nexus between human mobility and the environment

Abstract: Human mobility is increasingly associated with environmental and climatic factors. One way to explore how mobility and the environment are linked is to review the research on different aspects of the topic. However, so many relevant articles are published that analysis of the literature using conventional techniques is becoming prohibitively arduous. To overcome this constraint, we have applied automated textual analysis. Using unsupervised topic modelling on 3197 peer-reviewed articles on the nexus between mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
11
0
2
Order By: Relevance
“…After the screening process, we did a cross-reference check with other review articles on climate change migration (Cattaneo et al 2019;Beine and Jeusette 2021;Hoffmann et al 2020Hoffmann et al , 2021Thalheimer et al 2021;Zander et al 2022) to ensure we included all key literature, even if not found through our keyword search of the two databases. Through this process, we added 48 articles, leading to 387 articles in total.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…After the screening process, we did a cross-reference check with other review articles on climate change migration (Cattaneo et al 2019;Beine and Jeusette 2021;Hoffmann et al 2020Hoffmann et al , 2021Thalheimer et al 2021;Zander et al 2022) to ensure we included all key literature, even if not found through our keyword search of the two databases. Through this process, we added 48 articles, leading to 387 articles in total.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Amongst the hazards that are frequently concurrent are droughts and heatwaves, which occur over various timescales (Alizadeh et al 2020;Ribeiro et al 2020), and are increasingly being considered drivers of human mobility (Mastrorillo et al 2016;Mueller et al 2020). The literature on this field has been expanding rapidly (Zander et al 2022) to the extent that it can now be reviewed to understand the scope of the research already conducted and the gaps where further research would appear to be warranted.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations